2017
DOI: 10.1038/s41467-017-01832-6
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenan catabolism is encoded by a complex regulon in marine heterotrophic bacteria

Abstract: Macroalgae contribute substantially to primary production in coastal ecosystems. Their biomass, mainly consisting of polysaccharides, is cycled into the environment by marine heterotrophic bacteria using largely uncharacterized mechanisms. Here we describe the complete catabolic pathway for carrageenans, major cell wall polysaccharides of red macroalgae, in the marine heterotrophic bacterium Zobellia galactanivorans. Carrageenan catabolism relies on a multifaceted carrageenan-induced regulon, including a non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
172
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(181 citation statements)
references
References 78 publications
8
172
1
Order By: Relevance
“…In members of Bacteroidetes, these assemblages are known as Polysaccharide Utilization Loci (PULs) [40], and are recognized by the existence of tandem SusC/SusD transporter systems. Similar gene constellations absent of canonical SusC/SusD pairs have been reported in other phyla as well, including Gammaproteobacteria [41,42], and have recently lead to an update of the PUL term [40,42]. Closer inspection of contig 58 showed that the identified GH107 fucanase genes (fp273, fp277, and fp279) displayed such an organization ( Fig.…”
Section: Sequence Analysis Of Three Novel Endo-fucanases Provides Newsupporting
confidence: 72%
See 1 more Smart Citation
“…In members of Bacteroidetes, these assemblages are known as Polysaccharide Utilization Loci (PULs) [40], and are recognized by the existence of tandem SusC/SusD transporter systems. Similar gene constellations absent of canonical SusC/SusD pairs have been reported in other phyla as well, including Gammaproteobacteria [41,42], and have recently lead to an update of the PUL term [40,42]. Closer inspection of contig 58 showed that the identified GH107 fucanase genes (fp273, fp277, and fp279) displayed such an organization ( Fig.…”
Section: Sequence Analysis Of Three Novel Endo-fucanases Provides Newsupporting
confidence: 72%
“…Despite increased activities in next‐generation sequencing of the marine environment , public databases contain relatively few GH107 candidates. This small number is in contrast to CAZymes targeting other algal polysaccharides (e.g., carrageenases and alginate lyases), which are often highly abundant in the public databases . One possibility could be that bacteria carrying GH107s are specific to certain ecological niches, which have not been frequently investigated.…”
Section: Resultsmentioning
confidence: 99%
“…A pathway for the degradation of -carrageenan in strain A3 T showed similarity to the pathways in P. carrageenovora 9 T (29) and Z. galactanivorans (20). The -carrageenase Ce391 and possibly Ce392 hydrolyze -carrageenan to -neocarrabiose (DA2S-G4S), which subsequently may be desulfated by a DA2S sulfatase and a G4S sulfatase.…”
Section: Resultsmentioning
confidence: 81%
“…1). TonB-dependent receptors, previously proposed to be analogous to the Bacteroidetes detection system (10,19,20), were located in both gene clusters (Ce2863 and Ce345; Fig. 1).…”
Section: Resultsmentioning
confidence: 88%
“…Accessory genes, such as transcriptional regulators, transporter genes and sulfatases, are also often encoded by PULs. Recent studies showed the remarkable repertoires of CAZymes of Flavobacteriia (Hehemann et al ., ; Thomas et al ., ; Ficko‐Blean et al ., ), which are frequently associated with algae blooms (Teeling et al ., ; Williams et al ., ; Teeling et al ., ). Due to the large chemical diversity of algal polysaccharides, individual bacterial strains have adapted to utilize only selected polysaccharide subsets as energy and carbon sources (Landa et al ., ).…”
Section: Introductionmentioning
confidence: 99%